Resilience, Social Support, and Anxious Preoccupation in Patients with Advanced Cancer during COVID-19 Pandemic. (3rd July 2022) - Velasco-Durantez, Veronica; Jimenez-Fonseca, Paula; Martín Abreu, Carla M.; Ghanem, Ismael; González Moya, Manuel; Asensio, Elena; Corral, María J.; Rodriguez-Gonzalez, Adan; Gil-Raga, Mireia; Carmona-Bayonas, Alberto; Calderon, Caterina
Abstract: This study examines the mediating role of social support between anxious preoccupation and resilience in patients with cancer during COVID-19. NEOetic_SEOM is a prospective, multicenter study involving individuals with advanced, unresectable cancer who completed the following scales: Resilience (BCRS), Social Support (Duke-UNC-11), and anxious preoccupation subscale of the Mini-Mental Adjustment to Cancer (M-MAC) before starting antineoplastic treatment. Between March 2020 and July 2021, 507 patients (55% male; mean age, 65) were recruited. No differences in resilience were observed based on sociodemographic or clinical characteristics. Social support in people with advanced, unresectable cancer promotes both decreased anxious preoccupation and greater resilience.